Generalized moment representations and multivariate multipoint Padé-type approximants - Holub, A. P.; Pozharskiy, O. A.; Chernetska, L. O. (Ukrains’kyi Matematychnyi Zhurnal, 2026)
UDC 517.53 Dzyadyk’s method of generalized moment representations is used to construct and study bivariate two-point Pad\’e-type approximants.